Two-dimensional ultrathin graphene nanosheet and preparation method thereof

Preparation of two-dimensional ultra-thin graphene nanosheets by a one-step heat treatment method based on zinc-based metal organic frame materials has solved the problems of complex operation and low purity in the prior art, achieved efficient catalytic performance, and provided rich porosity and The loading site promotes the application of catalytic reactions.

CN119191281AActive Publication Date: 2024-12-27OCEAN UNIV OF CHINA
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411410877.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-27
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The prior art is complex in the preparation of two-dimensional ultrathin graphene nanosheets, with low product purity, and difficult to regulate the surface pores of materials and introduce catalytically active species, affecting their performance in catalytic reactions.

Method used

Two-dimensional ultra-thin graphene nanosheets were prepared by one-step heat treatment using zinc-based metal organic frame materials, and their one-dimensional channel structure and rich porosity were used as catalytic support.

Benefits of technology

A simple preparation process is achieved, product purity and production efficiency are improved, and a large number of exposed site-supported catalytic active substances are provided, which significantly improves the performance of catalytic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191281A_ABST
    Figure CN119191281A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of inorganic non-metallic materials, in particular to a two-dimensional ultrathin graphene nanosheet and a preparation method thereof. The two-dimensional ultrathin graphene nanosheet is prepared on the basis of a zinc-based metal organic framework material. According to the preparation method, based on the zinc-based metal organic framework material, preparation from the block MOF material to the two-dimensional ultrathin graphene nanosheet is completed in one step, the preparation steps are simple, operation is easy, the obtained product is high in purity, tedious aftertreatment is not needed, and the production efficiency of the product is improved. The obtained two-dimensional ultrathin graphene nanosheet material is stable in frame, ultrathin in structure and rich in pores, can be used as a firm carrier to provide a large number of exposed sites to load catalytic active substances, has excellent performance in various catalytic reactions, and is easy to popularize and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic non-metallic materials, and in particular to a two-dimensional ultra-thin graphene nanosheet and a preparation method thereof. Background Art

[0002] Low-dimensional nanomaterials have been widely studied in the fields of optics, catalysis, energy storage, etc. Among them, two-dimensional ultra-thin graphene nanosheets constructed from a few layers of atoms not only have the unique advantages of graphene, but also show the anisotropic characteristics of one-dimensional nanostructures, showing excellent physical and chemical properties. In recent years, the synthesis of graphene nanosheets usually adopts mechanical or chemical exfoliation, electrodeposition or bottom-up organic synthesis. However, in the actual application process, these traditional methods are found to be not only complicated to operate, time-consuming and labor-intensive, but also difficult to adjust the morphology and composition of the resulting products. Especially when used to construct catalytic materials, there are great difficulties in effectively regulating the pores on the surface of the material and the precise introduction of active species.

[0003] Metal-organic Framework (MOF) materials have an ordered crystal structure and porosity, a flexible framework structure, and precisely controllable active sites, making them very promising in synthesizing materials with specific structures. However, the preparation of two-dimensional carbon materials based on MOF materials still requires the pre-design of the two-dimensional MOF and the control of the morphology during the heat treatment process. Although the sonochemical treatment and activation of MOF-derived carbon nanorods can obtain two-dimensional graphene nanosheets, it also involves multiple processing steps, poor operability, and the resulting product has low purity, requiring further post-processing through cumbersome steps, and low product production efficiency.

[0004] Therefore, designing a simple and efficient method to complete the preparation of two-dimensional ultrathin graphene nanosheets from bulk MOF materials in one step without tedious post-processing has great application value, which can open up new avenues for the development of low-dimensional nanomaterials, but it is also a major challenge. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, the present invention provides a two-dimensional ultra-thin graphene nanosheet based on a zinc-based metal organic framework material and a preparation method thereof. A MOF material with a one-dimensional channel structure was synthesized and a two-dimensional ultra-thin graphene nanosheet was successfully prepared by a one-step heat treatment. The obtained two-dimensional ultra-thin graphene nanosheet has a stable framework, an ultra-thin structure, and rich pores. It can be used as a solid carrier to provide a large number of exposed sites for loading catalytic active substances. It has excellent performance in a variety of catalytic reactions and is easy to promote and use.

[0006] The technical solution of the present invention is:

[0007] A two-dimensional ultra-thin graphene nanosheet is prepared based on a zinc-based metal organic framework material.

[0008] Preferably, the method for preparing the above two-dimensional ultra-thin graphene nanosheets comprises the following steps:

[0009] S1. Dissolve zinc metal salt and 2,5-dihydroxyterephthalic acid organic monomer in organic solvents respectively, add the two solutions into a reactor to obtain a mixture, disperse the mixture evenly by ultrasonic wave, and then seal and heat. After the reaction is completed and cooled to room temperature, filter or centrifuge to separate the solid, wash with an organic solvent, and then dry to obtain a zinc-based metal organic framework material.

[0010] S2. The zinc-based metal organic framework material obtained in S1 is subjected to heat treatment, and after pyrolysis and cooling in an atmosphere, a two-dimensional ultrathin graphene nanosheet material is obtained.

[0011] Preferably, the mass ratio of the zinc metal salt to the 2,5-dihydroxyterephthalic acid organic monomer in S1 is (1-3):(1-4).

[0012] Preferably, the mass ratio of the zinc metal salt to the 2,5-dihydroxyterephthalic acid organic monomer in S1 is 1:1.

[0013] Preferably, the zinc metal salt in S1 is zinc acetate, zinc nitrate or zinc chloride.

[0014] Preferably, the reaction solvent is one or more of methanol, ethanol, n-butanol, n-hexane, and N,N-dimethylformamide.

[0015] Preferably, the reaction solvent is methanol and ethanol.

[0016] Preferably, the ultrasonic treatment time in S1 is 1 to 30 min.

[0017] Preferably, the ultrasonic treatment time in S1 is 5 min.

[0018] Preferably, the heating temperature of the reactor in S1 is 130-180° C., and the heating time is 6-24 hours.

[0019] Preferably, the heating temperature of the reactor in S1 is 150° C. and the heating time is 18 h.

[0020] Preferably, the washing solvent in S1 is methanol or ethanol, and the washing times are 3 to 6 times.

[0021] Preferably, the number of washings in S1 is 3 times.

[0022] Preferably, in S1, a non-zinc metal salt is added to the zinc metal salt to obtain an organic framework material loaded with the corresponding metal.

[0023] Preferably, iron is loaded in the finished graphene nanosheets by adding ferric chloride to the zinc metal salt solution.

[0024] Preferably, after obtaining the zinc-based metal organic framework material, a post-treatment is performed to obtain an organic framework material loaded with a non-zinc metal.

[0025] Preferably, the post-treatment method is a two-solvent method.

[0026] Preferably, the heat treatment temperature of the zinc-based metal organic framework material in S2 is 900-1100° C., and the treatment time is 0.5-4 h.

[0027] Preferably, the heat treatment temperature of the zinc-based metal organic framework material in S2 is 1000° C. and the treatment time is 2 h.

[0028] Preferably, the atmosphere is an inert atmosphere or an atmosphere required for element doping.

[0029] Preferably, the atmosphere required for element doping is ammonia. The generation of ammonia is obtained by simultaneously heat-treating the zinc-based metal organic framework material in S2 with a substance that generates ammonia.

[0030] The beneficial effects achieved by the present invention are:

[0031] 1. The present invention is based on zinc-based metal organic framework materials and completes the preparation from bulk MOF materials to two-dimensional ultra-thin graphene nanosheets in one step. The preparation steps are concise and the operation is simple. The obtained product has high purity and does not require tedious post-processing, thereby improving the production efficiency of the product.

[0032] 2. The two-dimensional ultra-thin graphene nanosheet material obtained by the present invention has a stable framework, ultra-thin structure, and rich pores. It can be used as a solid carrier to provide a large number of exposed sites for loading catalytic active substances. It has excellent performance in a variety of catalytic reactions and is easy to promote and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a flow chart of preparing two-dimensional ultra-thin graphene nanosheet material according to the present invention.

[0034] Figure 2 This is the preparation process of the two-dimensional ultrathin graphene nanosheet material obtained in Examples 1 to 7 of the present invention and the one-dimensional carbon nanorod material obtained in Comparative Examples 1 to 2.

[0035] Figure 3It is the X-ray diffraction (Powder X-ray Diffraction, PXRD) diagram of the metal organic framework material involved in the embodiments and comparative examples of the present invention.

[0036] Figure 4 It is a Powder X-ray Diffraction (PXRD) diagram of the two-dimensional ultrathin graphene nanosheet material obtained in the embodiment of the present invention and the one-dimensional carbon nanorod material obtained in the comparative example.

[0037] Figure 5 A is a scanning electron microscope (SEM) image of MOF-130T-(1:1) in an embodiment of the present invention.

[0038] Figure 5 B is a scanning electron microscope image of MOF-150T-(1:1) in an embodiment of the present invention.

[0039] Figure 5 C is a scanning electron microscope image of MOF-180T-(1:1) in an embodiment of the present invention.

[0040] Figure 5 D is a scanning electron microscope image of MOF-150T-(2:1) in an embodiment of the present invention.

[0041] Figure 5 E is a scanning electron microscope image of Fe@MOF-150T-(1:1) in an embodiment of the present invention.

[0042] Figure 5 F is a scanning electron microscope image of Fe-MOF-150T-(1:1) in an embodiment of the present invention.

[0043] Figure 5 G is a scanning electron microscope image of Fe-MOF-150T-(3:1) in an embodiment of the present invention.

[0044] Figure 5 H is a scanning electron microscope image of Fe-MOF-150T-(4:1) in an embodiment of the present invention.

[0045] Figure 6 A is a scanning electron microscope image of GNS-130T-(1:1) in an embodiment of the present invention.

[0046] Figure 6 B is a scanning electron microscope image of GNS-150T-(1:1) in an embodiment of the present invention.

[0047] Figure 6C is a scanning electron microscope image of GNS-180T-(1:1) in an embodiment of the present invention.

[0048] Figure 6 D is a scanning electron microscope image of GNS-150T-(2:1) in an embodiment of the present invention.

[0049] Figure 6 E is a scanning electron microscope image of Fe@NGNS-150T-(1:1) in an embodiment of the present invention.

[0050] Figure 6 F is a scanning electron microscope image of Fe-NGNS-150T-(1:1) in an embodiment of the present invention.

[0051] Figure 6 G is a scanning electron microscope image of CNR-150T-(3:1) in an embodiment of the present invention.

[0052] Figure 6 H is a scanning electron microscope image of CNR-150T-(4:1) in an embodiment of the present invention.

[0053] Figure 7 This is an atomic force microscope (AFM) image of the two-dimensional ultrathin graphene nanosheet material obtained in Example 2 of the present invention.

[0054] Figure 8 This is a scanning transmission electron microscopy (STEM) image of the two-dimensional ultrathin graphene nanosheet material obtained in Example 2 of the present invention;

[0055] Fig. 9 This is the nitrogen adsorption isotherm diagram of the two-dimensional ultrathin graphene nanosheet material obtained in Example 2 of the present invention

[0056] Fig.10 This is a pore size distribution diagram of the two-dimensional ultrathin graphene nanosheet material obtained in Example 2 of the present invention.

[0057] Fig.11 This is a performance diagram of the application of the nitrogen-doped iron-loaded two-dimensional ultrathin graphene nanosheet material obtained in Example 6 of the present invention in the oxygen reduction reaction.

[0058] Fig.12 This is a performance diagram of the application of the nitrogen-doped iron-loaded two-dimensional ultrathin graphene nanosheet material obtained in Example 6 of the present invention in the carbon dioxide reduction reaction. DETAILED DESCRIPTION

[0059] To facilitate those skilled in the art to understand the present invention, the specific embodiments of the present invention are described below in conjunction with the accompanying drawings. The experimental methods described in the examples are conventional methods unless otherwise specified. The reagents and materials described can be obtained from commercial sources unless otherwise specified.

[0060] It should be noted that in the following examples and comparative examples, for the convenience of recording, the MOF precursor material is named MOF-XT-(Y), where X is the synthesis temperature of MOF, and Y is the ratio of zinc salt to organic ligand. Correspondingly, graphene nano-sheets are named GNS-XT-(Y), and carbon nano-rods are named CNR-XT-(Y).

[0061] Example 1

[0062] S1. Dissolve 0.2g zinc acetate and 0.2g 2,5-dihydroxyterephthalic acid in 8mL methanol and 60mL ethanol respectively, then mix the two solutions in a solvent thermal reactor to obtain a suspension, and ultrasonicate the suspension for 5min to ensure that the mixed solution is evenly dispersed. Subsequently, seal the reactor and heat at 130°C for 24h. After cooling, centrifuge the solid and wash it 3 times with excess methanol. After drying, a brown-yellow metal organic framework material, MOF-130T-(1:1), is obtained.

[0063] S2. The metal organic framework MOF-130T-(1:1) obtained in S1 was placed in a tubular furnace, heated to 1000°C at a heating rate of 5°C / min under an Ar atmosphere and kept warm for 2 h. After cooling to room temperature, a two-dimensional ultrathin graphene nanosheet material based on the metal organic framework MOF-130T-(1:1) (denoted as GNS-130T-(1:1)) was obtained.

[0064] Example 2

[0065] S1. Dissolve 0.2g zinc acetate and 0.2g 2,5-dihydroxyterephthalic acid in 8mL methanol and 60mL ethanol respectively, then mix the two solutions in a solvent thermal reactor to obtain a suspension, and ultrasonicate the suspension for 5min to ensure that the mixed solution is evenly dispersed. Subsequently, seal the reactor and heat at 150°C for 18h. After cooling, centrifuge the solid and wash it 3 times with excess methanol. After drying, a brown-yellow metal-organic framework material, MOF-150T-(1:1), is obtained.

[0066] S2. The metal organic framework MOF-150T-(1:1) obtained in S1 was placed in a tubular furnace, heated to 1000°C at a heating rate of 5°C / min under an Ar atmosphere and kept warm for 2 h. After cooling to room temperature, a two-dimensional ultrathin graphene nanosheet material based on the metal organic framework MOF-150T-(1:1) (denoted as GNS-150T-(1:1)) was obtained.

[0067] Example 3

[0068] S1. Dissolve 0.2g zinc acetate and 0.2g 2,5-dihydroxyterephthalic acid in 8mL methanol and 60mL ethanol respectively, then mix the two solutions in a solvent thermal reactor to obtain a suspension, and ultrasonicate the suspension for 5min to ensure that the mixed solution is evenly dispersed. Subsequently, seal the reactor and heat at 180°C for 6h. After cooling, centrifuge the solid and wash it 3 times with excess methanol. After drying, a brown-yellow metal organic framework material, MOF-180T-(1:1), is obtained.

[0069] S2. The metal organic framework MOF-180T obtained in S1 was placed in a tubular furnace, heated to 1000°C at a heating rate of 5°C / min under an Ar gas atmosphere and kept warm for 2 h. After cooling to room temperature, a two-dimensional ultrathin graphene nanosheet material based on the metal organic framework MOF-180T (denoted as GNS-180T-(1:1)) was obtained.

[0070] Example 4

[0071] S1. Dissolve 0.4 g zinc acetate and 0.2 g 2,5-dihydroxyterephthalic acid in 8 mL methanol and 60 mL ethanol, respectively. Then mix the two solutions in a solvent thermal reactor to obtain a suspension, and ultrasonicate the suspension for 5 min to ensure that the mixed solution is evenly dispersed. Subsequently, seal the reactor and heat at 150 ° C for 18 h. After cooling, centrifuge the solid and wash it 3 times with excess methanol. After drying, a brown-yellow metal organic framework material, MOF-150T-(2:1), is obtained.

[0072] S2. The metal organic framework MOF-150T-(2:1) obtained in S1 was placed in a tubular furnace, heated to 1000°C at a heating rate of 5°C / min under an Ar atmosphere and kept warm for 2 h. After cooling to room temperature, a two-dimensional ultrathin graphene nanosheet material based on the metal organic framework MOF-150T-(2:1) (denoted as GNS-150T-(2:1)) was obtained.

[0073] Example 5

[0074] S1. Dissolve 0.2g zinc acetate and 0.2g 2,5-dihydroxyterephthalic acid in 8mL methanol and 60mL ethanol respectively, then mix the two solutions in a solvent thermal reactor to obtain a suspension, and ultrasonicate the suspension for 5min to ensure that the mixed solution is evenly dispersed. Subsequently, seal the reactor and heat at 150°C for 18h. After cooling, centrifuge the solid and wash it 3 times with excess methanol. After drying, a brown-yellow metal-organic framework material, MOF-150T-(1:1), is obtained.

[0075] S2. Place 1 g MOF-150T-(1:1) obtained in S1 and 2 g melamine in a tubular furnace, with melamine and the metal organic framework material at the upstream and downstream respectively. Heat to 1000 °C at a heating rate of 5 °C / min under Ar atmosphere and keep warm for 2 h. After cooling to room temperature, obtain nitrogen-doped two-dimensional ultrathin graphene nanosheet material based on the metal organic framework MOF-150T-(1:1) (denoted as NGNS-150T).

[0076] Example 6

[0077] S1. Dissolve 0.2g zinc acetate and 0.2g 2,5-dihydroxyterephthalic acid in 8mL methanol and 60mL ethanol respectively, then mix the two solutions in a solvothermal reactor to obtain a suspension, and ultrasonicate the suspension for 5min to ensure that the mixed solution is evenly dispersed. Subsequently, seal the reactor and heat at 150°C for 18h. After cooling, centrifuge the solid and wash it with excess methanol three times. After drying, a brown-yellow metal-organic framework material, namely MOF-150T-(1:1) is obtained; 1g MOF-150T-(1:1) is ultrasonically suspended in n-hexane, and an aqueous solution of ferric acetate is added dropwise. After the solution is completely absorbed, the solid is centrifuged and dried to obtain a brown-yellow metal-organic framework material with ferric acetate adsorbed inside, namely [Fe]@MOF-150T-(1:1).

[0078] S2. Place 1g [Fe]@MOF-150T obtained in S1 with iron acetate adsorbed inside and 2g melamine in a tubular furnace, with melamine and the metal organic framework material at the upstream and downstream respectively. Heat to 1000°C at a heating rate of 5°C / min under Ar atmosphere and keep warm for 2h. After cooling to room temperature, obtain a nitrogen-doped iron-loaded two-dimensional ultrathin graphene nanosheet material based on the metal organic framework MOF-150T-(1:1) (denoted as Fe / NGNS-150T-(1:1)).

[0079] Example 7

[0080] S1. Dissolve 0.2g zinc acetate and 0.2g 2,5-dihydroxyterephthalic acid in 8mL methanol and 60mL ethanol respectively, then mix the two solutions in a solvothermal reactor to obtain a suspension, add a methanol solution of ferric chloride to the suspension, and ultrasonicate the suspension for 5min to ensure that the mixed solution is evenly dispersed. Subsequently, seal the reactor and heat at 150°C for 18h. After cooling, centrifuge the solid and wash it 3 times with excess methanol. After drying, a brown-green metal organic framework material, Fe-MOF-150T-(1:1), is obtained.

[0081] S2. Place 1 g Fe-MOF-150T-(1:1) metal organic framework obtained in S1 and 2 g melamine in a tubular furnace, with melamine and the metal organic framework material at the upstream and downstream respectively. Heat to 1000°C at a heating rate of 5°C / min under Ar atmosphere and keep warm for 2 h. After cooling to room temperature, obtain a nitrogen-doped iron-loaded two-dimensional ultrathin graphene nanosheet material based on the metal organic framework MOF-150T-(1:1) (denoted as Fe-NGNS-150T-(1:1)).

[0082] Comparative Example 1

[0083] Compared with Example 1, the main difference is that the mass ratio of zinc metal salt to 2,5-dihydroxyterephthalic acid organic monomer is adjusted from 1:1 to 3:1.

[0084] S1. Dissolve 0.6g zinc acetate and 0.2g 2,5-dihydroxyterephthalic acid in 8mL methanol and 60mL ethanol, respectively. Then mix the two solutions in a solvent thermal reactor to obtain a suspension, and ultrasonicate the suspension for 5min to ensure that the mixed solution is evenly dispersed. Then, seal the reactor and heat at 150°C for 18h. After cooling, centrifuge the solid and wash it 3 times with excess methanol. After drying, a brown-yellow metal-organic framework material, MOF-150T-(3:1), is obtained.

[0085] S2. The metal organic framework MOF-150T-(3:1) obtained in S1 was placed in a tubular furnace, heated to 1000°C at a heating rate of 5°C / min under an Ar gas atmosphere and kept warm for 2 hours. After cooling to room temperature, a one-dimensional carbon nanorod material based on the metal organic framework MOF-150T-(3:1) (denoted as CNR-150T-(3:1)) was obtained.

[0086] Comparative Example 2

[0087] Compared with Example 1, the main difference is that the mass ratio of zinc metal salt to 2,5-dihydroxyterephthalic acid organic monomer is adjusted from 1:1 to 4:1.

[0088] S1. Dissolve 0.8g zinc acetate and 0.2g 2,5-dihydroxyterephthalic acid in 8mL methanol and 60mL ethanol respectively, then mix the two solutions in a solvent thermal reactor to obtain a suspension, and ultrasonicate the suspension for 5min to ensure that the mixed solution is evenly dispersed. Subsequently, seal the reactor and heat at 150°C for 18h. After cooling, centrifuge the solid and wash it 3 times with excess methanol. After drying, a brown-yellow metal-organic framework material, MOF-150T-(4:1), is obtained.

[0089] S2. The metal organic framework L-MOF-1 obtained in S1 was placed in a tubular furnace, heated to 1000°C at a heating rate of 5°C / min under an Ar atmosphere and kept warm for 2 h. After cooling to room temperature, a one-dimensional carbon nanorod material based on the metal organic framework MOF-150T-(4:1) was obtained (denoted as CNR-150T-(4:1)).

[0090] Figure 1 It is a flow chart of preparing two-dimensional ultra-thin graphene nanosheet material according to the present invention.

[0091] Figure 2 The preparation flow chart of Examples 1-7 and Comparative Examples 1-2 of the present invention shows that the composition of the metal organic framework is different but the material morphology structure is not significantly changed, and two-dimensional ultra-thin graphene nanosheet materials can be obtained. However, the change in the ratio of the synthetic raw materials will lead to differences in the material morphology, and the changed morphology structure makes it impossible to obtain a two-dimensional ultra-thin graphene nanosheet material.

[0092] Figure 3 is the X-ray diffraction of the MOF precursors involved in the embodiments and comparative examples of the present invention, Figure 4 The X-ray diffraction patterns of the two-dimensional ultrathin graphene nanosheet material obtained in the embodiment of the present invention and the one-dimensional carbon nanorod material obtained in the comparative example. In the derived carbon material spectrum, only two broad peaks appeared at about 24° and 44° for all four, corresponding to the (002) and (101) crystal planes of the graphene phase, respectively, indicating that the obtained derived materials have a high degree of carbonization and no zinc metal substances remain.

[0093] Figure 5 A-5H is a scanning electron microscope image of the MOF precursor material MOF-XT-Y (X=130, 150, 180; Y=(1:1), (2:1)) obtained in the examples of the present invention; Figure 6 A-6F is a scanning electron microscope image of the two-dimensional ultrathin graphene nanosheet material GNS-XT-Y (X=130, 150, 180; Y=(1:1), (2:1)) obtained in an embodiment of the present invention; Figure 5G-5H is a scanning electron microscope image of the MOF precursor material MOF-150T-Y (Y=(3:1), (4:1)) obtained in the comparative example of the present invention; Figure 6 G-6H is a scanning electron microscope image of the one-dimensional carbon nanorod material CNR-150T-Y (Y=(3:1), (4:1)) obtained in the comparative example of the present invention. The product obtained in the example shows a clear graphene nanosheet structure with an ultra-high exposure area. The product obtained in the comparative example shows a one-dimensional carbon nanorod structure with a smaller exposure area.

[0094] Figure 7 This is an atomic force microscope image of the two-dimensional ultrathin graphene nanosheet material obtained in Example 2 of the present invention, showing that the thickness of the graphene nanosheet is about 5 nm.

[0095] Figure 8 This is a scanning transmission electron microscope image of the two-dimensional ultrathin graphene nanosheet material obtained in Example 2 of the present invention, and the ultrathin structure of the graphene nanosheet can be clearly observed.

[0096] Fig. 9 This is a nitrogen adsorption isotherm diagram of the two-dimensional ultrathin graphene nanosheet material obtained in Example 2 of the present invention. Fig.10 The pore size distribution diagram of the two-dimensional ultrathin graphene nanosheet material obtained in Example 2 of the present invention shows a typical type II adsorption isotherm, indicating that the material presents a non-porous or macroporous structure. This is because the material presents an ultra-thin (~5nm) nanosheet structure; the isotherm is processed using the BET (Brunauer-Emmet-Teller) formula to obtain a specific surface area of ​​225m 2 / g, which is beneficial to the contact between the surface sites of the material and the surrounding environment and the transmission of substances.

[0097] Fig.11 This is a performance diagram of the application of the nitrogen-doped iron-loaded two-dimensional ultrathin graphene nanosheet material obtained in Example 6 of the present invention in the oxygen reduction reaction.

[0098] Fig.12 This is a performance diagram of the application of the nitrogen-doped iron-loaded two-dimensional ultrathin graphene nanosheet material obtained in Example 6 of the present invention in the carbon dioxide reduction reaction.

[0099] In summary, the two-dimensional ultrathin graphene nanosheet material prepared by the present invention has a stable framework, ultrathin structure and rich porosity, so that it can be used as a solid carrier to provide a large number of exposed sites for loading catalytic active substances, and is easy to promote and use.

[0100] The above-described embodiments of the present invention do not constitute a limitation on the protection scope of the present invention. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A two-dimensional ultrathin graphene nanosheet, characterized in that: The two-dimensional ultra-thin graphene nanosheet is prepared based on a zinc-based metal organic framework material.

2. The method for preparing a two-dimensional ultrathin graphene nanosheet according to claim 1, characterized in that: The steps include: S1. Dissolve a zinc metal salt and a 2,5-dihydroxyterephthalic acid organic monomer in an organic solvent respectively, add the two solutions into a reactor to obtain a mixture, disperse the mixture evenly by ultrasonic wave, and then seal and heat the mixture. After the reaction is completed and cooled to room temperature, filter or centrifuge to separate the solid, wash it with an organic solvent, and then dry it to obtain a zinc-based metal organic framework material; S2. The zinc-based metal organic framework material obtained in S1 is subjected to heat treatment, and after pyrolysis and cooling in an atmosphere, a two-dimensional ultrathin graphene nanosheet material is obtained.

3. The method for preparing a two-dimensional ultrathin graphene nanosheet according to claim 2, characterized in that: The mass ratio of the zinc metal salt and the 2,5-dihydroxyterephthalic acid organic monomer in S1 is (1-3):(1-4).

4. A method for preparing a two-dimensional ultrathin graphene nanosheet according to claim 2 or 3, characterized in that: The zinc metal salt in S1 is zinc acetate, zinc nitrate or zinc chloride; the reaction solvent is one or more of methanol, ethanol, n-butanol, n-hexane and N,N-dimethylformamide.

5. The method for preparing a two-dimensional ultrathin graphene nanosheet according to claim 2, characterized in that: The ultrasonic treatment time in S1 is 1 to 30 minutes.

6. The method for preparing a two-dimensional ultrathin graphene nanosheet according to claim 2, characterized in that: The heating temperature of the reactor in S1 is 130-180° C., and the heating time is 6-24 hours.

7. The method for preparing a two-dimensional ultrathin graphene nanosheet according to claim 2, characterized in that: The washing solvent in S1 is methanol or ethanol, and the washing times are 3 to 6 times.

8. The method for preparing a two-dimensional ultrathin graphene nanosheet according to claim 2, characterized in that: In S1, a non-zinc metal salt is added to a zinc metal salt to obtain an organic framework material loaded with the corresponding metal; or an organic framework material loaded with a non-zinc metal is obtained by post-processing the obtained zinc-based metal organic framework material.

9. The method for preparing a two-dimensional ultrathin graphene nanosheet according to claim 2, characterized in that: The heat treatment temperature of the zinc-based metal organic framework material in S2 is 900-1100° C., and the treatment time is 0.5-4 hours.

10. The method for preparing a two-dimensional ultrathin graphene nanosheet according to claim 2, characterized in that: The atmosphere is an inert atmosphere or an atmosphere required for element doping.

Citation Information

Patent Citations

  • Simple preparation method of graphene nanosheet and application thereof to cathode material of lithium ion battery

    CN108878884A

  • Composite material with high dielectric property and preparation method thereof

    CN109545549A

  • Preparation method and application of ferrocobalt bimetallic organic framework derived carbon material

    CN113422071A

  • Preparation method of N-doped Zn-MOF derived carbon skeleton material and supercapacitor

    CN115206695A

  • Preparation method of lithium ion battery negative electrode material graphite-like carbon

    CN117800334A